Proteomic analysis of up‐regulated proteins in human promonocyte cells expressing severe acute respiratory syndrome coronavirus 3C‐like protease - Lai, Chien‐Chen (Proteomics, 2007)
The pathogenesis of severe acute respiratory syndrome coronavirus (SARS CoV) is an important issue for treatment and prevention of SARS. Previously, SARS CoV 3C‐like protease (3CLpro) has been demonstrated to induce apoptosis via the activation of caspase‐3 and caspase‐9 (Lin, C. W., Lin, K. H., Hsieh, T. H., Shiu, S. Y. et al., FEMS Immunol. Med. Microbiol. 2006, 46, 375–380). In this study, proteome analysis of the human promonocyte HL‐CZ cells expressing SARS CoV 3CLpro was performed using 2‐DE and nanoscale capillary LC/ESI quadrupole‐TOF MS. Functional classification of identified up‐regulated proteins indicated that protein metabolism and modification, particularly in the ubiquitin proteasome pathway, was the main biological process occurring in SARS CoV 3CLpro‐expressing cells. Thirty‐six percent of identified up‐regulated proteins were located in the mitochondria, including apoptosis‐inducing factor, ATP synthase beta chain and cytochrome c oxidase. Interestingly, heat shock cognate 71‐kDa protein (HSP70), which antagonizes apoptosis‐inducing factor was shown to down‐regulate and had a 5.29‐fold decrease. In addition, confocal image analysis has shown release of mitochondrial apoptogenic apoptosis‐inducing factor and cytochrome c into the cytosol. Our results revealed that SARS CoV 3CLpro could be considered to induce mitochondrial‐mediated apoptosis. The study provides system‐level insights into the interaction of SARS CoV 3CLpro with host cells, which will be helpful in elucidating the molecular basis of SARS CoV pathogenesis.